Ectopic gall bladder: A case report - Amitabh Yadav; Samrat Ray; Samiran Nundy (SAGE Open Medical Case Reports, 2021)
Ectopic gall bladder under the left lobe of liver is a rare congenital anomaly of the position of gall bladder, which is mostly detected during surgery and causes technical difficulty at the time of operation. We operated a 64-year-old male who presented with gall stone disease and pre-operative ultrasound did not report any abnormality in position. On laparoscopy, it was found to be attached on the left side of falciform ligament under segment III. It was a true ectopic gall bladder without situs inversus. Early division of the falciform ligament and a careful and complete dissection of the gall bladder are advocated before clipping the cystic artery and duct to avoid complications. The present case report discusses about this rare anomaly and the available literature on the subject.